Metallogeny of gold and uranium as part of the growth and differentiation of the Neoproterozoic crust: the example of Mayo-Kebbi massif (Chad) in the orogenic belt of Central Africa - (:unkn) unknown (My University, 2015)
The Mayo Kebbi massiflocated in southwestern Chad between the Congo craton in the South, the West African craton in the west and the Sahara metacraton to the east exposes a segment of Neoproterozoic juvenile crust accreted in the Central African orogenic belt during the Pan African orogeny. It consists of two greenstone belts (Zalbi and Goueygoudoum) separated by the May Kebbi calc-alkaline batholith complexes and intruded by calc-alkaline high-K granitic plutons. The whole is covered by Phanerozoic sedimentary formations. The greenstone belts contain sulphide zones hosted mainly by metaplutonic rocks (granodiorites) and metabasalts and metavolcaniclastics. The mineralization comprises pyrite, pyrrhotite, arsenopyrite, chalcopyrite, pentlandite, pentlandite silver, pentlandite cobaltiferous, sphalerite, cobaltite. These sulphides are disseminated, aggregated in form of layers or are filling veins and cracks. The greenstones also contain quartz veins with calcite and chlorite comprising a mineralization made of pyrite, chalcopyrite, galena and gold. Gold is present both as native crystals and as electrum. The high-K calc-alkaline Zabili granitic pluton hosts uranium mineralization related to a superposition of: (1) ductile deformation and metasomatic alteration implying the interaction between magmatic minerals with a Na-rich fluid, of potential magmatic origin, coeval to the main deposition of uranium oxides, followed by (2) brittle deformation and deposition of secondary hydrated uranium silicates involving a Na-Ca-rich fluid. We propose that these uranium mineralizations represent the extreme expression of crustal differentiation as a result of Pan-African reworking of a Neoproterozoic juvenile crustal segment
Keywords: African Research